Giorgio Caproni. Bibliografia delle opere e della critica (1933-2020) - Baldini, Michela; Baldini, Michela (Florence Firenze University Press, 2021)
On the thirtieth anniversary of the death of Giorgio Caproni (Livorno 1912 - Roma 1990), this volume, through the expertise and work of Michela Baldini, proposes a very useful and necessary tool: a complete bibliography of/on Giorgio Caproni, from 1933 to 2020, with almost 4000 reports. The Antologia della critica concludes the volume, offering important studies on Caproni (Betocchi, Bo, Macrí, Dolfi, Ramat, Surdich, Zuliani).
Italian
Keywords: Giorgio Caproni; Bibliography; Literary Criticism; Twentieth Century